Information technology adoption for service innovation practices and competitive advantage: the case of financial firms - J.S. Chen; H.T. Tsou (Information Research: An International Electronic Journal)
Background. The importance of information technology to current business practices has long drawn the attention of practitioners and academicians. Aim. This paper aims to broaden understanding about service innovation as a critical organizational capability through which information technology adoption influences the competitive advantage of a firm. In the context of financial firms, this study examines how information technology is adopted and managed to enhance service innovation practices and whether and how service innovation practices may influence the competitive advantage of firms. Method. A research framework and the associated hypotheses are proposed. An empirical survey was conducted and questionnaires were mailed to 558 financial firms in Taiwan. Analysis. A total of 124 valid observations was collected and analysed using the partial least squares technique. Conclusion. . The results suggest that adopting information technology has positive effects on service innovation practices, which increase the competitive advantage of firms.